Toxicity of formaldehyde, and its role in the formation of harmful and aromatic compounds during food processing - Xiaoyan Sun; Chunmin Yang; Weiyue Zhang; Jie Zheng; Juanying Ou; Shiyi Ou (Food Chemistry: X)
Formaldehyde is a highly reactive compound known to pose several health risks, including carcinogenic, neurotoxic, reproductive, allergic, immunological, genetic, and respiratory toxicity. While its free concentration in processed foods is typically low even it can be formed through various biochemical and chemical pathways in foods. This study aims to investigate the fate of formaldehyde in food processing from two key perspectives: (1) its role in the formation of other harmful compounds, such as heterocyclic aromatic amines, methylimidazole, advanced glycation end-products, and N-nitrosamines, and (2) its potential to contribute to the generation of aromatic compounds, including oxygen-, sulfur-, and nitrogen-containing heterocyclic aromas. This review provides insights that may help food scientists develop strategies to mitigate formaldehyde's harmful effects while potentially harnessing its role in producing beneficial aromatic compounds.